PERSEPSI PENGUNJUNG KEDAI TEH SURAKARTEA PADA FENOMENA PEREMPUAN MEROKOK - Rahmaliana, Etika; Suryo S, Herning; Maria, Dewi (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Slamet Riyadi Surakarta, 2024)
The phenomenon of women smoking is a behavior that is difficult to overcome in a socialcontext. The people of Solo consider smoking inappropriate for women. The research wasconducted at the Surakartea tea shop using qualitative research methods. Data collectiontechniques include interviews, observation and documentation carried out directly. Thetechnique for determining informants was carried out by purposive sampling of seveninformants. The theory of perception in this research proceeds through five stages; stimulation,organization, interpretation and evaluation, memory and finally the process of recall. Theresults show that the perception of visitors to the Surakartea tea shop is that there is a badstigma attached to women smoking. This is considered because cigarettes are not identical tothe character of women who are known for their elegance, and are considered to be contraryto the values of religious teachings. Second, smoking has a negative impact on health or theenvironment. Third, smoking behavior is influenced by surrounding environmental conditions.As a result of selection regarding gender with religious teaching values in the phenomenon ofwomen smoking.Keywords: cigarettes, women, phenomenon, perception